VANCOMYCIN RESISTANT STAPHYLOCOCCUS AUREUS IN DR. WAHIDIN SUDIROHUSODO HOSPITAL MAKASSAR - Fatmawaty Ahmad; Nurhayana Sennang; Benny Rusli (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Vancomycin Resistant Staphylococcus aureus (VRSA) refers to bacteria that have complete resistance to Vancomycin. The increasing prevalence of VRSA can be a significant clinical problem with the limited therapeutic options. Therefore, the identification of VRSA is necessary to improve the management of antibiotic therapy, infection control and to prevent the occurrence of wider resistance. This retrospective descriptive study used secondary data of antibiotic susceptibility test on Staphylococcus aureus identified using VITEK 2 and patient medical records from January 2015 to December 2016. The data is processed using SPSS. Of 387 Staphylococcus aureus isolates obtained, 45 (11%) were VRSA. The most common VRSA isolates were male patients (57.8%) with the mean age being 41-60 years old (35.6%). The treatment ward with the most VRSA isolates were from surgical ward (20%), and internal medicine ward (15.6%) whereas the VRSA isolates from outpatient record were from surgical department (8.9%), dermatology department and ENT department (2.2%). The most common specimens were blood (28.9%), pus (26.7%), and sputum (20.0%). The highest prevalence of VRSA was found in the use of ≥ 3 invasive medical devices and from clinical outcome was found 11 (24.4%) of the patients died. Linezolid, Quinupristin / Dalfopristin, Tigecycline, and Nitrofurantoin as a therapeutic option have > 90% sensitivity. Identification of VRSA in Dr. Wahidin Sudirohusodo Hospital Makassar emphasized the need for immediate action by infection control division, especially in related units to prevent the transmission.